2010
DOI: 10.1186/1476-4598-9-115
|View full text |Cite
|
Sign up to set email alerts
|

Determination of genes and microRNAs involved in the resistance to fludarabine in vivo in chronic lymphocytic leukemia

Abstract: BackgroundChronic lymphocytic leukemia (CLL) cells are often affected by genomic aberrations targeting key regulatory genes. Although fludarabine is the standard first line therapy to treat CLL, only few data are available about the resistance of B cells to this purine nucleoside analog in vivo. Here we sought to increase our understanding of fludarabine action and describe the mechanisms leading to resistance in vivo. We performed an analysis of genomic aberrations, gene expression profiles, and microRNAs exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(49 citation statements)
references
References 57 publications
2
47
0
Order By: Relevance
“…We previously showed that the miR-221/222 cluster is upregulated in CLL cells by CpG treatment and modulates the expression of p27KIP1 protein (42). Of note, miR-221 and miR-222 were recently shown to play a key role in chemoresistance of solid tumors (43) and to be upregulated in vivo in patients with CLLs refractory to fludarabine treatment (44). Our previous data (42) suggest that the observed TLR-mediated drug resistance in CLL may also be influenced by upregulation of miR221/222 cluster.…”
Section: Discussionmentioning
confidence: 99%
“…We previously showed that the miR-221/222 cluster is upregulated in CLL cells by CpG treatment and modulates the expression of p27KIP1 protein (42). Of note, miR-221 and miR-222 were recently shown to play a key role in chemoresistance of solid tumors (43) and to be upregulated in vivo in patients with CLLs refractory to fludarabine treatment (44). Our previous data (42) suggest that the observed TLR-mediated drug resistance in CLL may also be influenced by upregulation of miR221/222 cluster.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, certain miRNAs are deregulated in CLL compared with normal B cells (23)(24)(25)(26), whereas distinct microRNA signatures are associated with prognostic factors and disease progression (24)(25)(26)(27)(28)(29), response to treatment (30,31) and various other disease characteristics (26,32,33).…”
mentioning
confidence: 99%
“…In a similar study involving 50 chronic lymphocytic leukemia patients, fludarabine resistance was associated with decreased miR-29a and increased miR-181a expression [28].…”
Section: For Reprint Orders Please Contact: Reprints@futuremedicinecommentioning
confidence: 92%